Research on the Coupling Coordination Mechanism of Innovation Ability and Financial Core Competitiveness of China’s Energy Enterprises under the Perspective of “Belt and Road” - Chen, Anxin; Yan, Ruikun (European Scientific Journal, ESJ, 2026)
Against the backdrop of global energy transition and the deepening implementation of the Belt and Road Initiative, China’s energy enterprises face dual challenges of technological innovation and financial sustainability. This study focuses on the dynamic coupling mechanism between the innovation capability and financial core competitiveness of energy enterprises. An empirical analysis of the dynamic relationships among eight Belt and Road energy enterprises from 2018 to 2024 is conducted by constructing an indicator evaluation system and applying the entropy method, TOPSIS method, coupling coordination model and grey relational analysis. The findings reveal that the innovation capability of selected large-scale Chinese state-owned energy enterprises shows a steady upward trend, while their financial core competitiveness exhibits cyclical fluctuations due to external environmental shocks. Meanwhile, the coupling coordination degree of the dual systems evolves through three stages: “low-level coupling, antagonistic improvement, and short-term adjustment,” reflecting the dynamic adaptation process between technology transfer efficiency and financial resource allocation. The results indicate that enhancing the precision of technology investment, improving cross-border financial coordination mechanisms, and optimizing institutional environments are key pathways to enhance the coupling efficiency of the dual systems. This study provides a quantitative analytical framework and strategic references for energy enterprises to achieve a virtuous interaction between "innovation and finance" in complex international environments.